KAJIAN STUNTING PADA ANAK BALITA BERDASARKAN POLA ASUH DAN PENDAPATAN KELUARGA DI KOTA BANDA ACEH - AL Rahmad, Agus Hendra; Miko, Ampera (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2016)
The prevalence of stunting in Aceh province on the national, the prevalence of stunting was 44,6%, Banda Aceh prevalence of 38.8%. They its become important to note the cause of the incident. The purpose study to assess the incidence of Stunting in children under five in terms exclusive breastfeeding, complementary feeding, immunization status, family characteristics. Quantitative research approaches to the design of Case Control Study, carried out in the region and Banda Raya Health Center, Batoh and Meuraxa the number of samples is 96. Data analysis includes univariate and bivariate using the Chi-square test on CI 95%, and multivariate (logistic regression). The result showed the incidence of stunting in infants caused by low family income (p= 0,026; OR= 3,1), non-exclusive breastfeeding (p= 0,002; OR= 4.2), giving poor complementary feeding (p= 0,007; OR= 3,4), and incomplete immunization (p= 0,040; OR= 3,5). Results of multivariate analysis obtained non-exclusive breastfeeding is very dominant cause stunting of children under five suffered Banda Aceh region with OR= 4,9. The conclusion, stunting among children is associated with lower family income, not-exclusively breastfeeding, complementary feeding less favorable and incomplete immunization. While not-exclusive breastfeeding a dominant factor as the cause of the child's risk of experiencing stunting.